Agentes infecto-parasitários transmitidos por carrapatos em pequenos mamíferos terrestres no Pantanal de Poconé, Mato Grosso, Brasil - Wolf, Rafael Willian (2015)
Ticks are parasites of a wide range of hosts that can transmit several pathogens. These parasites are responsible for the transmission of infectious agents such as bacteria of Rickettsia and Ehrlichia genus and also protozoa of Babesia and Hepatozoon genus. Previous reports show that Amblyomma, Ixodes and Rhipicephalus ticks genus can act as vectors in the transmission of these agents. Larvae and nymphs stages of the related ticks usually parasitize terrestrial small mammals while adults prey on large mammals. Taking into account the diversity of small terrestrial mammals of the Pantanal, the present study aimed to verify the occurrence of infection by Ehrlichia spp., Anaplasma spp., Rickettsia spp., Hepatozoon spp., Babesia spp. and parasitism by ticks in terrestrial small mammals of the Pantanal of Poconé region. Samples were collected in eight different habitats where sampling grids were installed containing 100 traps each. Samples of blood, liver and spleen were collected from animals captured. The detection of agents was performed by the Polymerase Chain Reaction (PCR). Sixty-four animals, marsupials and rodents were collected, and ten presented parasitism by ticks, one parasitized by Amblyomma cajennense, one by Amblyomma triste and eight by Argasidae. In the PCR analysis, one rodent (1.6%) was positive for the genus Anaplasma; three rodents (4,7%) were positive for Hepatozoon spp. and four (6,2%) were positive for Babesia spp., three of them (75%) were rodents and one (25%) was a marsupial. No animal presented positive result for Rickettsia spp. or Ehrlichia spp. After the sequencing analysis of positive samples, there was observed a fragment of 560 pb of 18S rRNA of Hepatozoon showed 99% of similarity with Hepatozoon sp. (FJ719819) detected in a marsupial species from Chile. For Babesia two distinct fragments of the 18S rRNA gene were amplified, one of 532 pb detected in a rodent and one of 556 pb detected in a marsupial. Both showed 95% of similarity with each other and were 97% similar to B. bicornis (AF419313).The results suggest that new genotypes or not described protozoa of the Babesia and Hepatozoon genus are present in the study area and small mammals may be acting as reservoirs for these agents in the Pantanal region.